Homecoming queers : desire and difference in Chicana Latina cultural production - Danielson, Marivel T. (Latinidad., 2009)
Homecoming Queers provides a critical discussion of the multiple strategies used by queer Latina authors and artists in the United States to challenge silence and invisibility within mainstream media, literary canons, and theater spaces. Marivel T. Danielson's analysis reveals the extensive legacy of these cultural artists, including novelists, filmmakers, students and activists, comedians, performers, and playwrights. By clearly discussing the complexities and universalities of ethnic, racial, sexual, gender, and class intersections between queer Chicana and U.S. Latinas, Danielson ex.